2017
DOI: 10.1186/s12936-017-1817-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacies of DHA–PPQ and AS/SP in patients with uncomplicated Plasmodium falciparum malaria in an area of an unstable seasonal transmission in Sudan

Abstract: BackgroundArtemisinin-based combination therapy (ACT), together with other control measures, have reduced the burden of falciparum malaria in sub-Saharan countries, including Sudan. Sudan adopted ACT in 2004 with a remarkable reduction in mortality due to falciparum malaria. However, emergence of resistance to the first-line treatment artesunate and sulfadoxine/pyrimethamine (AS/SP) has created new challenges to the control of malaria in Sudan. A search for an alternative drug of choice for treating uncomplica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…The other markers were not studied. The choice of DHA-PPQ as second line of treatment [17] is well supported by this evidence. PPQ enjoys the fact that it has never been used as a mono-therapy for malaria treatment [42,43].…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…The other markers were not studied. The choice of DHA-PPQ as second line of treatment [17] is well supported by this evidence. PPQ enjoys the fact that it has never been used as a mono-therapy for malaria treatment [42,43].…”
Section: Discussionmentioning
confidence: 59%
“…Earlier reports in Sudan have shown that multiple mutations were highly prevalent in eastern Sudan [7,14]. Failure of combination therapy AS/SP in Sudan was ascribed to failure of the partner drug SP [23] and that combination was replaced by AL as the first-line of treatment [17]. This high resistance of SP also means that it cannot be used intermittently for the protection of pregnant women in highly endemic areas in Sudan.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations